2018
DOI: 10.1093/nar/gky153
|View full text |Cite
|
Sign up to set email alerts
|

Protein-mediated loops in supercoiled DNA create large topological domains

Abstract: Supercoiling can alter the form and base pairing of the double helix and directly impact protein binding. More indirectly, changes in protein binding and the stress of supercoiling also influence the thermodynamic stability of regulatory, protein-mediated loops and shift the equilibria of fundamental DNA/chromatin transactions. For example, supercoiling affects the hierarchical organization and function of chromatin in topologically associating domains (TADs) in both eukaryotes and bacteria. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Recent chromosome conformation capture studies have revealed chromatin looping anchored by SMC proteins (condensin and cohesin) and self-association between similar epigenetically marked chromatin states as the two universal principles of structural and functional organization of eukaryotic genome (35). Remarkably, loops anchored by the SMC proteins could be strong enough to maintain a locally altered DNA supercoiling within a closed loop (36). Chromatin loops play an important functional role in mediating interactions between transcription-activating DNA elements such as enhancers and promoters (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Recent chromosome conformation capture studies have revealed chromatin looping anchored by SMC proteins (condensin and cohesin) and self-association between similar epigenetically marked chromatin states as the two universal principles of structural and functional organization of eukaryotic genome (35). Remarkably, loops anchored by the SMC proteins could be strong enough to maintain a locally altered DNA supercoiling within a closed loop (36). Chromatin loops play an important functional role in mediating interactions between transcription-activating DNA elements such as enhancers and promoters (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9]), that generate stretching and twisting forces on the chromosomal DNA [10][11][12][13][14][15]. It is also known that chromosomes form extensive adhesion contacts with a number of nuclear membrane proteins, establishing force-transmitting links between the chro-plexes (such as eukaryotic/archaeal histones) [23,24,35]; 2) DNA-bending proteins, which sharply curve DNA at the protein binding site (like bacterial HU, IHF and Fis) [22, 25-28, 30, 32, 36]; 3) DNA-bridging proteins that cross-link DNA duplexes (for example, bacterial H-NS, human HMGA2, or any other protein that mediates DNA loops) [29,[37][38][39], and 4) DNA-stiffening proteins forming rigid nucleoprotein filaments along DNA (like archaeal TrmBL2 and Alba) [31,33,40]. Thus, the four major groups of DNA-architectural proteins form nucleoprotein complexes, which have very different 3D structures, leading to diverse responses of these proteins to force and torque constraints applied to DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent experimental results ( 12 , 13 , 14 , 15 , 16 ), one may wonder whether DNA loops are ipso facto independent topological domains or whether some additional, more subtle properties of DNA-bridging proteins are required to achieve this goal. We emphasize that the word “loop” is used here according to its biological meaning and not the geometrical one.…”
Section: Resultsmentioning
confidence: 99%
“…The most straightforward explanation for this result is that two bridges in tandem are required to sustain the torque arising from the difference in torsional stress in the two DNA loops. Yet, single molecule experiments have demonstrated that a single LacI bridge can sustain the torque associated with physiological values of supercoiling, that is σ ≈ −0.06 ( 16 ). In this context, we surmise that the slow relaxation observed in ( 15 ) for single DNA bridges may correspond to the slow intrication obtained with our second model for DNA-bridging proteins, whereas the more stable topological separation observed in ( 15 ) for bridges in tandem corresponds to true barriers obtained with the third model for DNA-bridging proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation